Advances in Micro and Nano Manufacturing and Surface Engineering Proceedings of AIMTDR 2018 - Shunmugam, M. S.; Kanthababu, M. (Lecture Notes on Multidisciplinary Industrial Engineering, 2019)
This volume presents research papers on micro and nano manufacturing and surface engineering which were presented during the 7th International and 28th All India Manufacturing Technology, Design and Research conference 2018 (AIMTDR 2018). The papers discuss the latest advances in miniature manufacturing, the machining of miniature components and features as well as improvement of surface properties. This volume will be of interest to academicians, researchers, and practicing engineers alike.